Teachers’ Strategies in Integrating Faith and Learning at Faith-based Institutions of Higher Education in Asia - Lampadan, Naltan; Karau, Erwin; Maidom, Ritha (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Even though the concept of integrating faith and learning in the classroom is not only well-known but highly encouraged in Adventist educational institutions, observation shows that there are teachers who struggle to implement this effectively in their classrooms. One possible reason for the difficulty is the lack of knowledge regarding the various strategies that can be used in this area. As such, this study was conducted to discover practical strategies that teachers used in integrating faith and learning. The findings of this study can be useful to those who may want to know what real-life strategies other teachers used in integrating faith and learning. Purposive sampling was used in this study to ensure that participants would inform the research question. The participants of this study were 13 teachers who taught at four faith-based institutions in Thailand, Myanmar, and Taiwan. The participants’ average length of teaching experience is 11 years. The interview was the main method for generating the data, which were coded. The codes were analyzed through thematic analysis. This study found that participants employed various strategies in integrating faith and learning. The most common ones were illustrative, experiential, and contextual. Conceptual strategies were the least used. Keywords : Faith, Integration, Learning, Faith-based institution of higher education, Teachers